SPEECH DEVELOPMENT OF DEAF CHILDREN - Muhammadjonova Dilafruz Farhodjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article presents the categories of children with hearing impairment, the stages of speech development in children, speech development of deaf children, effective ways and methods of eliminating speech defects.